Detection and Sequence Diversity of Begomovirus Associated with Yellow Leaf Curl Disease of Pepper (Capsicum annuum) in West Sumatra, Indonesia - JUMSU TRISNO; SRI HENDRASTUTI HIDAYAT; TRIMURTI HABAZAR; ISHAK MANTI; . JAMSARI (Indonesian Society for microbiology, 2009)
Yellow leaf curl disease of pepper has become an emerging important disease in West Sumatra since early 2000. Several attempts have been made, including disease survey and detection, in order to identify the causal agent of the disease. Pepper (Capsicum annuum) plants showing yellow leaf curl from West Sumatra were analyzed for presence of Begomovirus employing Polymerase Chain Reaction (PCR) with degenerate primers pAL1v 1978 and pARc 715. A DNA fragment of 1.6 kb was successfully amplified and subjected to direct sequencing. A stem loop region was found in the nucleotide sequence obtained, which contains the conserved nucleotide signature sequence TAATATTAC present in begomoviruses. Based on the stem loop region comparisons and phylogenetic analysis, the virus isolates from West Sumatra showed the closest relationship to Pepper yellow leaf curl Indonesia virus (PYLVIV) and Tomato yellow leaf curl Indonesia virus (TYLCIV). The sequence was different from other Asia Begomoviruses reported earlier. These isolates were divided into three groups which were tentatively called Pepper yellow leaf curl Indonesia virus-West Sumatra-[group 1], -[group 2] and -[group 3] PYLCIV-WS-[group1], -[group2], and -[group3].